Hygroscopicity of pepper seeds (Capsicum chinense L.) - Silva, Hellismar W. da; Costa, Lilian M.; Resende, Osvaldo; Oliveira, Daniel E. C. de; Soares, Renato S. [UNESP]; Vale, Luis S. R. (Univ Federal Campina Grande, 2015)
The hygroscopicity in seeds provide essential information to optimize the drying process, storage and packaging development. The objective of this study was to determine the sorption isotherms of pepper seeds (Capsicum chinense L.), variety Cabacinha for different conditions of temperature and water activity. The sorption isotherms were determined at temperatures of 10, 20, 30 and 40 degrees C using the static indirect method and the water activity (aw) for each moisture content of seeds was determined by Hygropalm Model Aw1 equipment. The mathematical models often used to represent the hygroscopicity of agricultural products were adjusted to experimental data. For a constant water activity, increase in temperature decreased the equilibrium moisture content of pepper seeds. The desorption isotherms exhibit sigmoidal shape of type II. The models of Cavalcanti Mata, Clayton Chen, Chung Pfost, Modified Chung Pfost, Modified Henderson and Henderson are suitable to represent the hygroscopicity of seeds of pepper Cabacinha for the temperature range of 10 to 40 degrees C and water activity of 0.213 to 0.975.
Keywords: cabacinha; isotherms of desorption; modeling mathematic